2014
DOI: 10.1007/s10900-014-9977-9
|View full text |Cite
|
Sign up to set email alerts
|

Data for Program Management: An Accuracy Assessment of Data Collected in Household Registers by Community Health Workers in Southern Kayonza, Rwanda

Abstract: Community health workers (CHWs) collect data for routine services, surveys and research in their communities. However, quality of these data is largely unknown. Utilizing poor quality data can result in inefficient resource use, misinformation about system gaps, and poor program management and effectiveness. This study aims to measure CHW data accuracy, defined as agreement between household registers compared to household member interview and client records in one district in Eastern province, Rwanda. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Among the appropriately quantitative approaches, it is useful to analyse the treatment of Mitsunaga et al (2015), which provides a focus on the accuracy of data in household registries by health workers in Rwanda. The study envisaged the possibility of creating a data quality assessment system based on indicators related to demography and women's health.…”
Section: Quantitative Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the appropriately quantitative approaches, it is useful to analyse the treatment of Mitsunaga et al (2015), which provides a focus on the accuracy of data in household registries by health workers in Rwanda. The study envisaged the possibility of creating a data quality assessment system based on indicators related to demography and women's health.…”
Section: Quantitative Approachmentioning
confidence: 99%
“…To this end the results belonging to the collections of Taylor & Francis (Bai et al, 2018), BioMed Central (Ledikwe et al, 2014), Springer (Mitsunaga et al, 2015), Journal of Health Management & Informatics (Firouraghi et al, 2018), BioMed Central (Skyttberg et al, 2016), Elsevier (Verma, 2014), Oxford University Press (Watson et al, 2017), American College of Healthcare Executives (Wills, 2014) and National Institutes of Health (NIH) Health Care Systems Research Collaboratory (Zozus M. N., et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitsunaga et al reported an overall 'largely good' accuracy of the DSA across lowest administrative units (known as cells), with varying results by indicator. From their findings, there is potential for the routinely-collected data by CHWs to be meaningful inputs for strengthening the community health program management [15,16].…”
Section: Community-based Interventions For Maternal Health In Rwandamentioning
confidence: 99%